Are Four Simple Questions Able to Predict Weight Loss in Outpatients With Metastatic Cancer? A Prospective Cohort Study Assessing the Simplified Nutritional Appetite Questionnaire. (3rd July 2016) - Helfenstein, Seth F.; Uster, Alexandra; Rühlin, Maya; Pless, Miklos; Ballmer, Peter E.; Imoberdorf, Reinhard
ABSTRACT: Background : Severe weight loss is directly responsible for up to one-fifth of all cancer deaths and has a major impact on quality of life. The simplified nutritional appetite questionnaire (SNAQ) was validated to predict weight loss within 6 mo in community-dwelling adults and nursing home residents. Methods : We prospectively assessed the SNAQ in 133 palliative cancer outpatients. The SNAQ predictions were validated after 3 and 6 mo with the observed weight change. In addition, the treating oncologists gave their predictions concerning future weight loss according to their clinical judgment. Results : A significant weight loss of 5% of the original body weight within 6 mo occurred in 20 (24%) of the 133 patients. The SNAQ predicted weight loss with a sensitivity of 0.38 and a specificity of 0.66 ( P -value 0.81). The treating oncologists predicted weight loss with a sensitivity of 0.67 and a specificity of 0.7 ( P -value 0.002). Conclusion : The SNAQ does not represent a useful tool to predict impending weight loss in palliative cancer outpatients. The predictions of the treating oncologists were more reliable than those from the SNAQ, but remain poor. Better methods to predict weight loss in this patient group are therefore required.